Cu nanoparticles constrain segmental dynamics of cross-linked polyethers: a trade-off between non-fouling and antibacterial properties. Issue 13 (8th March 2019) - Nikitin, Daniil; Madkour, Sherif; Pleskunov, Pavel; Tafiichuk, Renata; Shelemin, Artem; Hanuš, Jan; Gordeev, Ivan; Sysolyatina, Elena; Lavrikova, Alexandra; Ermolaeva, Svetlana; Titov, Valerii; Schönhals, Andreas; et al.
Abstract : Copper nanoparticles induce constraints to segmental dynamics of poly(ethylene oxide) macromolecules which influence non-fouling/antibacterial properties of Cu/PEO nanocomposite films. Abstract : Copper has a strong bactericidal effect against multi-drug resistant pathogens and polyethers are known for their resistance to biofilm formation. Herein, we combined Cu nanoparticles (NPs) and a polyether plasma polymer in the form of nanocomposite thin films and studied whether both effects can be coupled. Cu NPs were produced by magnetron sputtering via the aggregation in a cool buffer gas whereas polyether layers were synthesized by Plasma-Assisted Vapor Phase Deposition with poly(ethylene oxide) (PEO) used as a precursor. In situ specific heat spectroscopy and XPS analysis revealed the formation of a modified polymer layer around the NPs which propagates on the scale of a few nanometers from the Cu NP/polymer interface and then transforms into a bulk polymer phase. The chemical composition of the modified layer is found to be ether-deficient due to the catalytic influence of copper whereas the bulk polymer phase exhibits the chemical composition close to the original PEO. Two cooperative glass transition phenomena are revealed that belong to the modified polymer layer and the bulk phase. The former is characterized by constrained mobility of polymer segments which manifests itself via a 30 K increase of dynamic glass transition temperature. Furthermore, the modified layer is characterized by the heterogeneous structure which results in higher fragility of this layer as compared to the bulk phase. The Cu NPs/polyether thin films exhibit reduced protein adsorption; however, the constrained segmental dynamics leads to the deterioration of the non-fouling properties for ultra-thin polyether coatings. The films are found to have a bactericidal effect against multi-drug resistant Gram-positive Methicillin -Resistant Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa .